Evaluation of the Transverse Carpal Ligament in Carpal Tunnel Syndrome by Shear Wave Elastography: A Non-Invasive Approach of Diagnosis and Management - Wu, Huaiyu; Yang, Keen; Chang, Xin; Liu, Zhaokang; Ding, Zhimin; Liang, Weiyu; Xu, Jinfeng; Dong, Fajin (Frontiers in Neurology, 2022)
Objectives: The goal of this work is to determine the clinical value of transverse carpal ligament (TCL) in carpal tunnel syndrome (CTS) for guiding subsequent treatment. Methods: This study analyzed patients who underwent median nerve (MN) ultrasound examination of the wrist from April 2020 to April 2021. The cross-sectional area and anteroposterior diameter of the MN, as well as the TCL thickness and stiffness were measured from images. The intra-groups and intra-patient subgroups differences were compared using t-test and rank test. We also utilized receiver operating characteristic curves to diagnose CTS and evaluate the severity. Result: The final cohort consisted of 120 wrists (bilateral) from 60 samples, evenly balanced across the patient and control groups according to their CTS diagnosis. In the unilateral positive patient subgroup, the MN and TCL of the positive hand were significantly thicker and stiffer than the negative counterparts (both, P < 0.05). The values from the right were also thicker and stiffer than the left (both, P < 0.05) in bilateral CTS patients. The MN and TCL of the patient group were also significantly thicker and stiffer than those of the control group (both, P < 0.001). For diagnosing CTS, the AUC of TCL thickness and stiffness at the distal carpal tunnel ranged between 0.925 to 0.967. For evaluating CTS severity, we found that the optimal TCL stiffness is sufficient for diagnosing mild and non-mild patient cases (AUC: Emean=0.757, Emax=0.779). Conclusions: Shear wave elastography is therefore an effective method for the CTS diagnosis and management.